Mizna: Prose Poetry, and Art exploring Arab America, vol 19.2, 2018/ The Palestine Issue (3eRfIs (Minnesota; Mizna, Inc., 2019)
Mizna is a nonprofit arts organization that promotes contemporary expressions of Arab American culture. Mizna is an Arabic word describing a desert cloud that holds the promise of rain and respite. Guest edited by Ismail Khalidi. Visual Art by Yazan Khalili.
English
Keywords: N5300-7418 Visual Arts- History; Palestine